2003
DOI: 10.1103/physrevlett.91.027002
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Nanocrystalline SuperconductingPbMo6S8with a Very Large Upper Critical Field

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…loss filamentary conductors made with YBCO. A number of improvements are possible in high density nanocrystalline YBCO materials: Flux pinning is expected to be very strong in high density, nanocrystalline samples prepared by ball milling [11][12][13]; The grain boundaries may be very clean due to the improved diffusion under high pressure; The densification of the material can improve the connectivity between grains thereby increasing J C [15,16], and the upper critical field (B C2 ) in the nano-structured superconductors may be increased by shortening the electron mean-freepath as has been found in the conventional superconductors such as Chevrel phase [11], elemental [17] and A15 compounds [18]. Improving B C2 of YBCO is particularly important for high magnetic field applications operating at liquid nitrogen temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…loss filamentary conductors made with YBCO. A number of improvements are possible in high density nanocrystalline YBCO materials: Flux pinning is expected to be very strong in high density, nanocrystalline samples prepared by ball milling [11][12][13]; The grain boundaries may be very clean due to the improved diffusion under high pressure; The densification of the material can improve the connectivity between grains thereby increasing J C [15,16], and the upper critical field (B C2 ) in the nano-structured superconductors may be increased by shortening the electron mean-freepath as has been found in the conventional superconductors such as Chevrel phase [11], elemental [17] and A15 compounds [18]. Improving B C2 of YBCO is particularly important for high magnetic field applications operating at liquid nitrogen temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the maximum observed enhancement is 2-3 T at 4.2 K. 3 In this Letter, we report that greater improvements in µ 0 H c2 (0) can be realized by introducing disorder instead of by alloying. Niu and Hampshire showed recently that highenergy ball milling of PbMo 6 S 8 superconductors, followed by controlled annealing in a hot isostatic press, resulted in a tripling of H c2 ′ at the expense of a modest reduction of T c from 15 to 12 K. 4 The µ 0 H c2 (0) values estimated by the WHH formula increased from 45 to 110 T. Based on this result, we explored whether a similar behavior could be induced in Nb 3 Sn.Past experiments have shown that the superconducting properties of Nb 3 Sn are optimized for compositions found at the tin-rich (stoichiometric) edge of the phase field. 5 Even for the stoichiometric composition, the superconducting properties are very sensitive to atomic site disorder introduced by irradiation or strain, 6 suggesting that the decrease in T c due to disorder might more than offset the benefit from the increase of H c2 ′.…”
mentioning
confidence: 99%
“…Hence, the maximum observed enhancement is 2-3 T at 4.2 K. 3 In this Letter, we report that greater improvements in µ 0 H c2 (0) can be realized by introducing disorder instead of by alloying. Niu and Hampshire showed recently that highenergy ball milling of PbMo 6 S 8 superconductors, followed by controlled annealing in a hot isostatic press, resulted in a tripling of H c2 ′ at the expense of a modest reduction of T c from 15 to 12 K. 4 The µ 0 H c2 (0) values estimated by the WHH formula increased from 45 to 110 T. Based on this result, we explored whether a similar behavior could be induced in Nb 3 Sn.…”
mentioning
confidence: 99%
“…Nevertheless, the developments in powder-in-tube technology means that long-length multifilamentary Nb 3 (Al 1-x Ge x ) wires may now be possible. According to BCS theory, B C2 (0) for a superconductor at zero temperature is given by [11]:…”
Section: Introductionmentioning
confidence: 99%